Vitamin D Deficit as Inducer of Adenotonsillar Hypertrophy in Children with Obstructive Sleep Apnea-A Prospective Case-Control Study - Pietro De Luca; Arianna Di Stadio; Pasquale Marra; Francesca Atturo; Alfonso Scarpa; Claudia Cassandro; Ignazio La Mantia; Antonio Della Volpe; Luca de Campora; Domenico Tassone; Angelo Camaioni; Ettore Cassandro (MDPI AG, 2023)
(1) Objective: This prospective case-control study aimed to assess the level of serum vitamin D comparing pediatric non-allergic patients with obstructive sleep apnea (OSA) and healthy controls. (2) Methods: The period of the enrollment was from November 2021 to February 2022. Children with uncomplicated OSA caused by adenotonsillar hypertrophy (ATH) were recruited. Allergy was excluded by skin prick test (SPT), and the determination of serum IgE level using ELISA test. Plasma concentration of 25-hydroxy vitamin D (25-OHD) was quantitatively determined; then, the vitamin D concentration in patients was compared with healthy controls matched for sex, age, ethnicity, and characteristics. (3) Results: Plasma 25-OHD levels were significantly lower in patients than in healthy subjects (mean 17 ng/mL, 6.27 DS, range 6-30.7 ng/mL, vs. mean 22 ng/mL, 9.45 DS, range 7-41.2 ng/ ml; p < 0.0005). The prevalence of children with vitamin D deficiency was significantly higher in the ATH group than controls. The plasma 25-OHD level did not change following the ATH clinical presentation (III or IV grade according to the Brodsky scale), while the different categories of 25-OHD status (insufficiency, deficiency, and adequacy) in the ATH group were statistically significantly different (p < 0.001) from healthy controls. (4) Conclusions: This study identified statistically significant differences between the ATH group and control regarding the plasma concentration of vitamin D; this data, despite not being directly linkable to the lymphoid tissue hypertrophy (p-value not significant), might suggest a negative effect of vitamin D deficit on the immune system.